Session-specific effects of the Metacognitive Training for Obsessive-Compulsive Disorder (MCT-OCD). (18th May 2020) - Miegel, Franziska; Cludius, Barbara; Hottenrott, Birgit; Demiralay, Cüneyt; Sure, Anna; Jelinek, Lena
Abstract: Objective: Most studies focus on overall treatment effects by assessing symptom severity before and after treatment, but few investigate session-specific effects of an intervention. The aim of the present study was to elucidate session-specific effects of a group therapy for obsessive-compulsive disorder (OCD) that targets cognitive biases known as the Metacognitive Training for OCD (MCT-OCD). Method: In an uncontrolled pilot trial, 44 inpatients with OCD participated in the MCT-OCD once a week over four weeks. Before and after each session, patients answered questionnaires on thought monitoring, control of thoughts, obsessions, compulsions, and mood. Results: Primary analyses using linear mixed-effect models showed that the module on control of thoughts (within-session effect) significantly reduced patients' control of thoughts. Exploratory analyses displayed an improvement in thought monitoring, control of thoughts, obsessions, and compulsions over the treatment period. Control of thoughts decreaed after the module on biased attention/biased cognitive networks and compulsions reduced one week after the module on overestimation of threat/responsibility (between-session effect). More compulsions were reported one week after the module on thought-action fusion/control of thoughts. Conclusions: Certain MCT-OCD modules seemed to improve specific cognitive biases that might in turn act as mechanisms of change. The results are being used to revise the MCT-OCD.